The Relationship Of Economic Status With The Motivation Of Dentistry In The New Normalera In Sukarami Village - Ismalayani; Salfiyadi, Teuku (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Socioeconomic status is one of the factors that affect the health status of the community or family. The economic level of a family will have a major influence on the sustainability of family members, both from the level of education and health. High socio-economic groups of people can access health services and take care of their family's health properly, on the contrary, people who are in low socio-economic groups tend to give priority to fulfilling their needs. daily needs rather than thinking about maintaining health and getting good health services. Objective: This study aims to determine the relationship between economic status and motivation for dental treatment in the New Normal Era in Sukarami Village, RT.03 Method: This research is an analytical survey research with a cross-sectional approach using a simple random sampling technique, carried out in February March 2022, The community of RT 03 in Sukarami sub-district as many as 100 people, the data were analyzed using the chi-square test. Results: In the univariate test, 41 respondents (41.0%) had a high economic status, a little compared to 59 (59.0%) respondents who had a low economic status. Meanwhile, 48 people had high motivation for dental treatment (48). %) is less than respondents who have low motivation as many as 52 people (52.09%). In the statistical test, the P-value = 0.000 <0.05 means that there is a significant relationship between economic status and motivation for dental treatment. dental treatment in the new normal era